![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(^{=x^3-3x^2+5x^2-15x+9x-27}\)
\(=x^2\left(x-3\right)+5x\left(x-3\right)+9\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
\(x^3+2x^2-6x-27\)
\(=x^3+5x^2+9x-3x^2-15x-27\)
\(=x\left(x^2+5x+9\right)-3\left(x^2+5x+9\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
ts cld b lv ag
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(x^3-x^2-5x+125\)
\(=\left(x^3+125\right)-\left(x^2+5x\right)\)
\(=\left(x+5\right)\left(x^2-5x+25\right)-x\left(x+5\right)\)
\(=\left(x+5\right)\left(x^2-5x+25-x\right)\)
\(=\left(x+5\right)\left(x^2-6x+25\right)\)
b ) \(x^3+2x^2-6x-27\)
\(=\left(x^3-27\right)+\left(2x^2-6x\right)\)
\(=\left(x-3\right)\left(x^2+3x+9\right)+2x\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2+3x+9+2x\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
a) x3 - x2 - 5x + 125
=(x3-6x2+25x)+(5x2-30x+125)
=x(x2-6x+25)+5(x2-6x+25)
=(x+5)(x2-6x+25)
b) x3 + 2x2 - 6x - 27
=x3+5x2+9-3x2-15x-27
=x(x2+5x+9)-3(x2+5x+9)
=(x-3)(x2+5x+9)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x3 - x2 - 5x + 125
=(x3-6x2+25x)+(5x2-30x+125)
=x(x2-6x+25)+5(x2-6x+25)
=(x+5)(x2-6x+25)
b) x3 + 2x2 - 6x - 27
=x3+5x2+9-3x2-15x-27
=x(x2+5x+9)-3(x2+5x+9)
=(x-3)(x2+5x+9)
c) 12x3 + 4x2 - 27x - 9
=4x2(3x+1)-9(3x+1)
=(4x2-9)(3x+1)
=[(2x)2-32](3x+1)
=(2x-3)(2x+3)(3x+1)
a) \(x^3-x^2-5x+125\)
\(=\left(x^3+125\right)-\left(x^2+5x\right)\)
\(=\left(x+5\right)\left(x^2-5x+25\right)-x\left(x+5\right)\)
\(=\left(x+5\right)\left(x^2-5x+25-x\right)=\left(x+5\right)\left(x^2-6x+25\right)\)
b) \(x^3+2x^2-6x-27\)
\(=\left(x^3-27\right)+\left(2x^2-6x\right)\)
\(=\left(x-3\right)\left(x^2+3x+9\right)+2x\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2+3x+9+2x\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
c) \(12x^3+4x^2-27x-9\)
\(=4x^2\left(3x+1\right)-9\left(3x+1\right)\)
\(=\left(3x-1\right)\left(4x^2-9\right)=\left(3x-1\right)\left(2x-3\right)\left(2x+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 6x2 - 11x + 3
= 6x2 - 9x - 2x + 3
= 3x ( 2x - 3 ) - ( 2x - 3 )
= ( 2x - 3 ) ( 3x - 1 )
b ) 2x2 + 3x - 27
= 2x2 - 6x + 9x - 27
= 2x ( x - 3 ) + 9 ( x - 3 )
= ( x - 3 ) ( 2x + 9 )
c ) 2x2 - 5xy - 3y2
= 2x2 - 2xy - 3xy - 3y2
= 2x ( x - y ) - 3y ( x - y )
= ( x - y ) ( 2x - 3y )
Ta có:
a) 6x2 - 11x +3 = 2x(3x-1)-3(3x-1)=(2x-3)(3x-1)
b) 2x2 +3x - 27= x(2x+9)-3(2x+9)=(x-3)(2x+9)
c) 2x2 -5xy-3y2 = 2x(x-3y)+y(x-3y)=(2x+y)(x-3y)
![](https://rs.olm.vn/images/avt/0.png?1311)
81-(x2+6x)2
=92-(x2+6x)2
=(9+x2+6x)(9-x2-6x)
=(x+3)2(9-x2-6x)
27-64a3
=33-(4a)3
=(3-4a)[32+3*4a+(4a)2]
=(3-4a)( 9+12a+16a2)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(6x^2-x-1\)
\(=6x^2-3x+2x-1\)
\(=3x\left(2x-1\right)+\left(2x-1\right)\)
\(=\left(3x+1\right)\left(2x-1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\)
\(4x^2-y^2+2x+y\)
\(=\left(4x^2-y^2\right)+\left(2x+y\right)\)
\(=\left(2x-y\right)\left(2x+y\right)+\left(2x+y\right)\)
\(=\left(2x+y\right)\left(2x-y+1\right)\)
\(b)\)
\(x^3+2x^2-6x-27\)
\(=x^3+5x^2+9x-3x^2-15x-27\)
\(=x\left(x^2+5x+9\right)-3\left(x^2+5x-9\right)\)
\(=\left(x-3\right)\left(x^2+5-9\right)\)
\(c)\)
\(12x^3+4x^2-27x-9\)
\(=\left(12x^3+4x^2\right)-\left(27x+9\right)\)
\(=4x^2\left(3x+1\right)-9\left(3x+1\right)\)
\(=\left(3x+1\right)\left(4x^2-9\right)\)
\(=\left(3x+1\right)[\left(2x\right)^2-3^2]\)
\(=\left(3x+1\right)\left(2x-3\right)\left(2x+3\right)\)
\(d)\)
\(16x^2+4x-y^2+y^2\)
\(=16x^2+4x\)
\(4x\left(4x+1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b)3x^2-18x+27=3x^2-9x-9x+27=3x*(x-3)-9*(x-3)=(x-3)*(3x-9)=(x-3)*3*(x-3)=3*(x-3)^2
c)x^3-4x^2-12x+27=(x+3)*(x^2-3x+9-4)=(x+3)*(x^2-3x+5)
d)27x^3-1/27=(3x-1/3)*(9x^2-x+1/9) (hang dt)
con a) voi e) mk chiu
=>A=x3-3x2+5x2-15x+9x-27
lấy x-3 chung
=>A=(x2+5x+9)(x-3)
\(x^3+2x^2-3x-27\)
\(=x^3-3x^2+5x^2-15x+9x-27\)
\(=x^2\left(x-3\right)+5x\left(x-3\right)+9\left(x-3\right)\)
\(=\left(x^2+5x-9\right)\left(x-3\right)\)